2018
DOI: 10.3390/cryst8020089
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structural Determination of SrAlD5 with Corner-Sharing AlD6 Octahedron Chains by X-ray and Neutron Diffraction

Abstract: Aluminium-based complex hydrides (alanates) composed of metal cation(s) and complex anion(s), [AlH 4 ] − or [AlH 6 ] 3− with covalent Al-H bonds, have attracted tremendous attention as hydrogen storage materials since the discovery of the reversible hydrogen desorption and absorption reactions on Ti-enhanced NaAlH 4 . In cases wherein alkaline-earth metals (M) are used as a metal cation, MAlH 5 with corner-sharing AlH 6 octahedron chains are known to form. The crystal structure of SrAlH 5 has remained unsolve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Ca(AlH 4 ) 2 and Sr(AlH 4 ) 2 form intermediate structures with the compositions CaAlH 5 and SrAlH 5 . Both compounds could be successfully synthesized in the deuterated forms and the complete crystal structures could be analyzed by neutron diffraction experiments [62,67] . Also BaAlD 5 could be prepared and the crystal structure could be solved [68] .…”
Section: Alkaline Earth Metal Aluminum Hydridesmentioning
confidence: 99%
See 1 more Smart Citation
“…Ca(AlH 4 ) 2 and Sr(AlH 4 ) 2 form intermediate structures with the compositions CaAlH 5 and SrAlH 5 . Both compounds could be successfully synthesized in the deuterated forms and the complete crystal structures could be analyzed by neutron diffraction experiments [62,67] . Also BaAlD 5 could be prepared and the crystal structure could be solved [68] .…”
Section: Alkaline Earth Metal Aluminum Hydridesmentioning
confidence: 99%
“…The SrAlD 5 structure was recently published by Sato et al in space group Pbcm instead of space group Pnma [67,64] . Pommerin et al described the crystal structure in Pnma but structure analysis was based on X-ray powder diffraction data und could therefore not determine hydrogen positions.…”
Section: Alkaline Earth Metal Aluminum Hydridesmentioning
confidence: 99%
“…Indeed, Pbcm-NaSiH 5 , which is isostructural to BaAlH 5 (Figure 2) (Zhang et al, 2002), was found on the convex hull. At the same time, a different octahedral chain structure, Pna2 1 -NaSiH 5 [isostructural to SrAlH 5 (Sato et al, 2018)], is only about 0.15 eV/Z less stable (Figure 2). It can be speculated that the composition NaSiH 5 gives rise to a manifold of enthalpically close-lying polymorphic structures (Weidenthaler et al, 2006;Shlyapnikov et al, 2018) and that, most likely, the most stable one has yet to be identified.…”
Section: Resultsmentioning
confidence: 99%
“…SrAlD 5 was produced by the mechanical milling of SrD 2 and AlD 3 and further heating at 154 °C for 1 h in Ar [229]. SrAlD 5 was studied by synchrotron and neutron diffraction in detail; the resolved structure consists of (AlD 6 ) octahedra that share corner D atom forming a chain (Figure 17) [229]. This was the first complete experimental report on the crystallography of SrAlD 5 (Table 10).…”
Section: The “Single Metal” Alanatesmentioning
confidence: 99%